Pointing in cervical dystonia patients - Tramonti Fantozzi, Maria Paola; Benedetti, Roberta; Crecchi, Alessandra; Briscese, Lucia; Andre, Paolo; Arrighi, Pieranna; Bonfiglio, Luca; Carboncini, Maria Chiara; Bruschini, Luca; Bongioanni, Paolo; Faraguna, Ugo; Manzoni, Diego (Frontiers in Systems Neuroscience, 2023)
The normal hemispheric balance can be altered by the asymmetric sensorimotor signal elicited by Cervical Dystonia (CD), leading to motor and cognitive deficits. Directional errors, peak velocities, movement and reaction times of pointing toward out-of-reach targets in the horizontal plane were analysed in 18 CD patients and in 11 aged-matched healthy controls. CD patients displayed a larger scatter of individual trials around the average pointing direction (variable error) than normal subjects, whatever the arm used, and the target pointed. When pointing in the left hemispace, all subjects showed a left deviation (constant error) with respect to the target position, which was significantly larger in CD patients than controls, whatever the direction of the abnormal neck torsion could be.Reaction times were larger and peak velocities lower in CD patients than controls. Deficits in the pointing precision of CD patients may arise from a disruption of motor commands related to the sensorimotor imbalance, from a subtle increase in shoulder rigidity or from a reduced agonists activation. Their larger left bias in pointing to left targets could be due to an increased right parietal dominance, independently upon the direction of head roll/jaw rotation which expands the left space representation and/or increases left spatial attention. These deficits may potentially extend to tracking and gazing objects in the left hemispace, leading to reduced skills in spatial-dependent motor and cognitive performance.